﻿Redescription of Rhacophorus tuberculatus (Anderson, 1871) and the validity of Rhacophorus verrucopus Huang, 1983 - R. S. Naveen; Shuo Liu; S. R. Chandramouli; S. Babu; P. V. Karunakaran; Honnavalli N. Kumara (Herpetozoa, 2023)
Rhacophorus tuberculatus and Rhacophorus verrucopus are two morphologically similar species described in 1871 and 1983 respectively. Their taxonomic distinctiveness has been questioned in the past. In the current study, we encountered frogs that we confer to R. tuberculatus based on morphological similarity to a syntype of this species. We redescribe the species based on a re-examination of a syntype, which is designated as a lectotype here, and additional specimens from Garo hills of Meghalaya. We also present molecular data, natural history notes, and report a range extension of this species. Molecular phylogenetic analysis based on the 16S rRNA fragment revealed minimal genetic divergences (0.20–1.74% uncorrected p-distance) between specimens identified as either R. tuberculatus or R. verrucopus from different locations. On the basis of molecular data and morphological characteristics, we conclude that R. verrucopus is a junior synonym of R. tuberculatus.